TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN BIMBINGAN TUGAS AKHIR - Asep Nursangaji; Hamdani Hamdani (Jurnal AlphaEuclidEdu, 2020)
Nowadays, there are several universities in West Kalimantan that have mathematics education department, such as IKIP Pontianak, STKIP Singkawang, and STKIP Sintang. This condition provides great opportunities for prospective students who want to become mathematics teachers in schools, especially high schools. On the other side, the presence of mathematics education department in several universities in West Kalimantan is a challenge for Mathematics Education department FKIP Untan. One of the challenges that come is how to produce graduates who can compete in the world of work. In order to create qualified mathematics teacher candidates, it is very important for the FKIP Untan mathematics education department to provide one of the quality final assignment guidance services so that final year students can have quality final projects. This study will examine how high the level of student satisfaction with final assignment guidance services in Mathematics Education Department FKIP Untan. Furthermore, it will be known what service items should be improved and developed in an effort to increase student satisfaction. The level of student satisfaction with the final assignment guidance service is 0% of students are not satisfied, 0% of students are not satisfied, 9% of students are satisfied, 30% of students are quite satisfied, and 61% of students are very satisfied. It can be concluded that the final year students of the Mathematics Education Department, Teaching and Education Faculty, Tanjungpura University are satisfied with the services provided by the supervisorsKeywords: Satisfaction; academic services; final assignment guidance.